Serum Anticholinergic Activity: A Possible Peripheral Marker of the Anticholinergic Burden in the Central Nervous System in Alzheimer's Disease. (9th February 2014) - Hori, Koji; Konishi, Kimiko; Tani, Masayuki; Tomioka, Hiroi; Akita, Ryo; Kitajima, Yuka; Aoki, Mari; Yokoyama, Sachiko; Azuma, Kazunari; Ikuse, Daisuke; Akashi, Norihisa; Hosoi, Misa; et al.
Abstract : We review the utility of serum anticholinergic activity (SAA) as a peripheral marker of anticholinergic activity (AA) in the central nervous system (CAA). We hypothesize that the compensatory mechanisms of the cholinergic system do not contribute to SAA if their system is intact and that if central cholinergic system deteriorates alone in conditions such as Alzheimer's disease or Lewy body dementia, CAA and SAA are caused by way of hyperactivity of inflammatory system and SAA is a marker of the anticholinergic burden in CNS. Taking into account the diurnal variations in the plasma levels of corticosteroids, which are thought to affect SAA, it should be measured at noon or just afterward.